Trade Liberalization and Developing Countries under the Doha Round - J. Francois; H. van Meijl; F. van Tongeren (Tinbergen Institute, 2003)
We explore the impact of multilateral liberalization, with emphasison distributional effects across countries. We first develop a realistic base1ine that takes into account events such as the entry of China into the WTO and the enlargement of the EU, allowing us to focus on those effects that are specifically attributable to further trade liberalization in the Doha Round. We then employ a global applied general equilibrium model, featuring capital accumulation and imperfect competition. Our Doha scenarios include agriculture, manufactures, and services liberalization, and trade facilitation. With agglomeration, OECD agricultural liberalization is not uniform1y positive for developing countries.
Keywords: F13; F4; F12; 330; WTO; Doha Round; trade liberalization; services trade; trade facilitation; CGE modeling; Handelsliberalisierung; Agraraußenhandel; Dienstleistungshandel; WTO-Recht; EU-Mitgliedschaft; Theorie; Entwicklungsländer; Welt; CGE-Modelling